Digital democracy during COVID-19 pandemic: use of information and communications technology between creativity and inability to promote the practice of democratic values. Case study of Jordan - Alquraan, Sultan N.; Adouse, Haytham (Creativity Studies, 2024)
This study aims to examine the extent to which information and communications technology was used as a tool for political socialization and promotion of democratic values, and the purpose and extent of Jordanian university students’ use of information and communications technology during the COVID-19 pandemic. The study adopted a cross-sectional design. A total of 1171 students were selected from science and humanities faculties at three universities to participate in the study. Questionnaires were sent to some of the university students to distribute to other students through their electronic learning platforms. The findings of the study revealed that, although most participants used information and communications technology to “high” and “very high” extents, they did not use it to promote democratic values, as the purpose was mainly for education, entertainment, and other services.